Urban transportation and logistics : health, safety, and security concerns - Taniguchi, Eiichi; Fwa, Tien Fang, 1951-; Thompson, Russell G., 1962- (2013)
"Urban transport and logistics systems play a very important role in delivery goods and services both into populous areas as well as out to local and regional areas. This book takes global approach to best practices, covering topics such as hazmat transport, logistics during disasters, mixed traffic and safety considerations, optimizing vehicle routing and scheduling, and road safety. These subjects provide an important basis for discussing transport and logistics systems in urban areas from the viewpoint of safety and security considerations on human life. "--
"Preface Urban transport and logistics systems play a very important role in human security engineering, since they provide basic components for ensuring the safety and security of human life in urban areas. Most of the activities of people in business and leisure depend greatly on the services of urban transport and logistics systems. However, we face difficult and complicated problems of efficiency, environment, energy consumption, safety relating to urban transport, and logistics in normal cases as well as in disasters. Therefore, understanding the problems, finding approaches and solutions, implementing them, and evaluating results are essential for creating better urban planning and policy implementation. This textbook aims to provide advanced knowledge and experience on urban transport and logistics for human security engineering. It includes a wide range of subjects - Concepts and vision for urban transport and logistics relating to human security - Transport and logistics in Asian cities - Healthy transport - Hazardous material transport - Mixed traffic in Asian cities - Road safety - Network design for freight transport and supply chain - Vehicle routing and scheduling with uncertainty - Urban transport and logistics in natural disasters - Application of ICT (information and communication technology) and ITS (intelligent transport systems) - Future perspectives on urban freight transport These subjects provide an important basis for discussing transport and logistics systems in urban areas from viewpoints of safety and security of human life. The ideas and knowledge included in these subject areas are relatively new but are very useful for creating innovative solutions to tackle real problems in urban areas"--
Includes bibliographical references and index.
Keywords: Urban transportation; Urban transportation -- Planning; Urban transportation -- Safety measures; Freight and freightage -- Planning; Delivery of goods -- Planning